Scientific Thinking About Legal Truth - Rosenzweig, Gal (Frontiers in Psychology, 2022)
In the criminal process, the fact finders assess the validity of impressions reported by witness-es based on their own perceptions, and determine what has happened in reality. But these im-pressions are not subject to any external validity check. The Innocence Project revealed the failure of this subjective method and showed how it can lead to innocent convictions. The legal literature has been examining ways to manage the risk of mistakes, but these ways are incon-sistent with scientific understanding about the need for external validity measurements. Which suggest new ways of thinking about the legal search for truth and justice.